Electronic Extortion and Its Impact on University Female Students: Pemerasan Elektronik dan Dampaknya terhadap Mahasiswi - Kareem , Afkar Fadhil (Indonesian Journal on Health Science and Medicine, 2025)
A descriptive study has been carried out in the period from 26 February till10 March 2021. The sample was collected using an electronic form. In a random way in the colleges of Bab Al-Zubir. This study consists of 448 female participant, the questionnaire consists of questions include socio-demographic question and questions about If the student was subjected to electronic extortion, the relationship with the extorter And if the distance from God, the weakness of family bound and the misuse of social media are among the causes of the problem, in the event that unemployment, weak financial condition or behavioral disturbance and instability are among the motives of the extortion, and the opinion of student among the effect of extortion like anxiety and lack of focus, isolation and dissocializing, fear of scandal, loss of appetite, shortness of breath and sleeplessness, the possibility of the girl to be killed by the parents and if extortion exposes the girl to suicide. The last part was including the type of relationship with the extorter, the type of extortion, the extortion materials, and what are the means that the student can take if she extorts, and what are her motives for reporting the blackmailer. The majority of students were youngest than 23 age. Most of the students live in district areas. (60.7%) of responders from College of Education for women, the majority of responders at third grade, Family monthly income of (44.4%) of responder's was ranged between 300-600 thousand id, (86.8%) of responder's Parent marital status was both of them alive, Also the majority of student were single. The majority of student's father education level were diploma degree and above. The majority of student's mother education level were primary school degree. (43.5%) of student's father job was employee, (87.1%) of student's mother job was housewife. Only (8.9%) of students were subjected to electronic extortion. (40.8%) of students knew people had subjected to electronic extortion. Only (5.8%) of the answers were There is relation with extorter. (86.4%) of answers agreed that electronic extortion becomes a social phenomenon. The main four causes of electronic extortion in our community were the negative use of social media, emptiness, and absence of goals, weak family bond, the lack of family supervision and follow-up of children according to the opinion of (94.6%, 89.3%, 89.1%, 87.7%) of participants. The main three effects of electronic extortion were attempting to suicide, fear of scandal, frequent monitoring of social media for fear of spreading victim's information by extorter, according to the opinion of (90%, 82.1%, 77.2%) of the participants. The main motive of electronic extortion was behavioral disorder and social media instability according to the opinion of (82.8%) of participants. (93.5%) of participants agreed that is possible for a girl to be killed by her family as a victim of electronic extortion. (94.4%) of participants agreed that the victim may expand negative thinking about what will happen if her personal information had spread to the public. Only (61.3%) of participant agreed that thinking of extortion as a temporary matter help to calm the victim. According to student the main 2 types of relationship between victim and extorter were electronic relationship and there is no relationship (33.7%, 47.1%). The main materials used for electronic extortion were all the material (video, photo and audio record), and photos (72.8%, 21%). the main types of electronic extortion were all the types (money, emotional and sexual extortion) to the opinion of (65.8%) of participant. The main ways to deal with electronic extortion were inform the stakeholders, (58%).the main motives for reporting of an extorter were According to the opinion of participants. (48.7%) all the motive as (to get rid of the problem, victim's fear of scandal and revenge). Highlights: Reveals psychological effects of electronic extortion on female students. Social media misuse and weak family bonds are main causes. Reporting to authorities is key response strategy. Keywords: electronic, extortion, impact, university female students